Environmental Footprint of Inland Fisheries: Integrating LCA Analysis to Assess the Potential of Wastewater-Based Microalga Cultivation as a Promising Solution for Animal Feed Production (2023)
This study evaluated the environmental impacts of producing 1 kg of biomass for animal feed grown in inland fisheries effluents as a culture medium using the ReCiPe method. Four scenarios with two downstream alternatives were modeled using the life cycle assessment method: Algal Life Feed (ALF), Algal Life Feed with Recycled nutrients (ALF+Rn), Pelletized Biomass (PB), and Pelletized Biomass with Recycled nutrients (PB+Rn). The findings reveal a substantial reduction in environmental impacts when wastewater is employed as a water source and nutrient reservoir. However, the eutrophication and toxicity-related categories reported the highest normalized impacts. ALF+Rn emerges as the most promising scenario due to its reduced energy consumption, highlighting the potential for further improvement through alternative energy sources in upstream and downstream processes. Therefore, liquid waste from fish production is a unique opportunity to implement strategies to reduce the emission of nutrients and pollutants by producing microalgae rich in various high-value-added metabolites.